The Inconsistency Effect of Anomalies on the Muslim Eid (Id Fitri) towards Abnormal Return : Case Study in the Indonesia Stock Exchange - Muhammad Abdul Ghoni (Institut Agama Islam Negeri (IAIN) Curup, 2019)
Purposes: The purpose of this paper is to analyze the causes of inconsistency in the effect of the